INCLUSÃO ESCOLAR DO ADOLESCENTE COM DEFICIÊNCIA INTELECTUAL NA REDE PÚBLICA DE ENSINO: percepções dos pais - Pinto, Maisa Cunha (2013)
This research presents a study on school inclusion of adolescents with intellectual disabilities in public schools from the perceptions of parents. With the purpose to understand the general perception of parents (caregivers) about the process of school inclusion of their adolescent children with intellectual disabilities, who are enrolled in the Educational Service Specialist ESA, the research included theoretical contributions of Freud (1996a, 1996b, 1996c, 1996d, 1996e, 1996f, 1996g, 1996h, 1996i, 1996j, 1996k) and Vigotsky (2007; 2008; 2010). Methodologically forms part of the field of qualitative research, in the category Case Study. The subjects were parents (caregivers) who had teenage son or daughter with intellectual disabilities enrolled in municipal public schools in São Luís - MA and the ESA. From the understanding of inclusive education as a complex issue that interweaves social, political, economic and cultural aspects worldwide, the research is justified in the face of current relevance to produce and share knowledge that will contribute to the development of inclusive education in the municipality of São Luís - MA, in particular for allowing a view of the process of school inclusion from parents. That way, required deeper understanding of the dynamics of the school, and family, the stage of development which comprises adolescence and the peculiarities of adolescents with intellectual disabilities. The results showed that parents are unaware of the process of school inclusion, even when they are present in the school. Have very little expectation for the schooling of their children. They consider care of room multifunction capabilities - SRM good, with an emphasis on attention and affection given in this space. While in the regular classroom, the educational needs of their children are not being met. Not identified moments of inclusion and exclusion was appointed as, for example, denied enrollment for three consecutive years in a regular classroom isolation and disrespect on the part of employees. Before their reports, we observed the perception of parents indicate that several factors have prevented the action inclusive schools mentioned. Are communication difficulties, lack of dialogue or lack of understanding of the information transmitted between health professionals and parents, administrators, teachers, parents and students, teachers of SRM regular classroom, school staff and students. Discrepancies between doing school and educational policies of inclusion. Difficulties in accommodating the student with intellectual disabilities, because there is no understanding of the line between difference and equality, the process of adolescence, the possibilities and demands of the cognitive construction of students with intellectual disabilities and, more seriously, the lack of knowledge perpetuates stigmas and prejudices about intellectual disability. In addition to the foregoing considerations, the research for his character investigation - in depth - has raised other issues not behaved in this work, but they raise new restlessness. These may cause future dialogue with academic productions and pursuing research important.